FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Jessica Stephanie, Yanti (Jurnal Paradigma Akuntansi, 2020)
The objective of this study is to obtain an empirical evidence about the effect of intellectual capital, sales growth, capital structure, and working capital management on firm performance in manufacturing companies which listed on Indonesian Stock Exchange on 2016- 2018. Sample was selected using purposive sampling method amounted to 42 manufacturing companies that met the criteria. Data processing techniques using multiple regression analysis that helped with E-views 10.0 program. The results showed intellectual capital and working capital management have a significant impact on firm performance while sales growth and capital structure showed an insignificant impact.